Estudo preliminar do teste Test for Creative Thinking-Drawing Production (TCT-DP) - Almeida, Leonor (2010)
We intent to do a preliminary study of the test TCT-DP - Test of Creative Thinking and Drawing Production of Urban e Jellen (1986), that aims an holistic evaluation of the divergent thinking. The test (Forms A and B) is based on some fragments of pictures which the subjects must complete freely. Our sample, collected among certain Lisbon Human Resourses Consultant Companies, involves 169 adult (over 18 years old) portuguese workers with diverse Literary and Professional competences. Beyond some aspects of the instrument adaptation to the portuguese population, some studies were made about que psychometric properties of the instrument with our sample. This study pointed out some clues for further studies, and sugests the enlargement of the sample as well their diversification.